Dylematy i konflikty moralne polityków i lekarzy w ustanawianiu zadań systemu opieki zdrowotnej - Gałuszka, Mieczysław (Annales. Etyka w Życiu Gospodarczym, 2008)
Medicine is the field of knowledge and set of clinical practices, characterized by the presence of politics and ethics on all the levels. Politics should be treated as a domain of power, which aims to make strategic decisions concerning health of the citizens leading to form socially accepted objectives of health care policy. Ethics sets axiological frames for morally just decisions both political and medical in the field of health care. The article analyzes the reasons of conflicts and moral dilemmas in the health care system. Decisions which are made within health care system should accomplish five criteria: medical, economical, social, legal and axiological. The term “moral panic” is used to illustrate situations concerning corruption and moral atrophy of doctors.